CCTV use by local government: findings from a national survey - Anthony Morgan
This paper presents the findings from a national survey of local government to develop a national picture of the prevalence and characteristics of open-street CCTV systems in Australia managed by local councils. Introduction There has been considerable growth in the use of closed circuit television (CCTV) in public spaces as a crime prevention measure and, increasingly, as a tool to detect and identify offenders. In Australia, CCTV systems have become an increasingly common fixture in urban centres, in shopping centres and malls, individual shops and banks, on public transport and in car parks. There has been significant investment in CCTV systems as part of state, territory and Commonwealth government crime prevention programs, with CCTV accounting for a growing proportion of overall grant funding available to community-based organisations, particularly local councils. More than a decade ago, Wilson and Sutton explored the operation and management of 33 open-street CCTV systems in Australia. They found that, while open street CCTV systems were initially primarily located in central business districts of major metropolitan centres, there was a growing trend towards their installation in smaller regional and rural centres and in suburban locations. Around the same time, Iris Research conducted a survey of all local councils in Australia to assess the use of CCTV and characteristics of the systems in operation, finding that around one in ten councils had a CCTV system in operation. More recently, Carr examined the use of CCTV by 18 local councils funded by the Australian Government, finding that police were increasingly reliant on local government CCTV and that the ensuing additional cost to council was significant. Similarly, Edmonds found that nearly half of all councils in NSW (46%; n=70) had installed CCTV in public spaces, with urban councils more than twice as likely than rural councils to have a system in place. Given the continued investment in CCTV at all levels of government plus the significant advances in technology over the past ten years, it is timely to reassess the use of CCTV by local councils in Australia. This paper presents the findings from a national survey of local government. The overall aim of this research was to develop a national picture of the prevalence and characteristics of open-street CCTV systems in Australia managed by local councils